2012
DOI: 10.1002/rem.21324
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of goods, services and eco‐cultural attributes of Native Americans and Caucasians in Idaho

Abstract: Understanding perceptions of how people value environmental resources is critical to conservation and management of ecosystems. We used interviews to examine perceptions and valuations of goods, services, and eco-cultural attributes of Native Americans and Caucasians attending an American Indian festival. The Native Americans interviewed were younger, achieved lower levels of education, and had lower mean incomes than did the Caucasians. There were no significant differences in the percentage of Native America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The character of natural ecosystems fundamentally and uniquely underly the traditional cultural and spiritual perspectives of Idaho indigenous tribes. For instance, Burger (2012) found that Bannock‐Shoshoni tribal members were more likely to value complex ecosystem characteristics (e.g., food chains) and emergent processes (e.g., species diversity) than local Caucasians in Idaho. Tribal perspectives, however, have become increasingly incorporated into management decisions concerning resources on western public lands, and may be further influenced and informed by reliable SEZs for these regions.…”
Section: Discussionmentioning
confidence: 99%
“…The character of natural ecosystems fundamentally and uniquely underly the traditional cultural and spiritual perspectives of Idaho indigenous tribes. For instance, Burger (2012) found that Bannock‐Shoshoni tribal members were more likely to value complex ecosystem characteristics (e.g., food chains) and emergent processes (e.g., species diversity) than local Caucasians in Idaho. Tribal perspectives, however, have become increasingly incorporated into management decisions concerning resources on western public lands, and may be further influenced and informed by reliable SEZs for these regions.…”
Section: Discussionmentioning
confidence: 99%